DASAR PERTIMBANGAN DI DALAM PRA PENATAAN RUANG KAWASAN RAWAN BENCANA DI WILAYAH PESISIR - Edyanto, C.B. Herman (Badan Pengkajian dan Penerapan Teknologi (BPPT), 2003)
Coastal is a fragile area where some physical development actions were taken by the people and thus may change the environment totally. There is no awareness of the local people to take care their environment surrounding from the detrimental processes, such as land, water or air pollutions. Coastal environment must, however, be protected from the ecosystem damaging. A river was identified as a mediator of water pollution from industries situated along the river which produce solid and liquid waste through flow of the river. Spatial planning, therefore, can manage the use of land for certain activities in both up and down streams of a river and other coastal regions to mitigate the hazard in the coast.